Improving the Post-Stroke Therapeutic Potency of Mesenchymal Multipotent Stromal Cells by Cocultivation With Cortical Neurons: The Role of Crosstalk Between Cells. (9th July 2015) - Babenko, Valentina A.; Silachev, Denis N.; Zorova, Ljubava D.; Pevzner, Irina B.; Khutornenko, Anastasia A.; Plotnikov, Egor Y.; Sukhikh, Gennady T.; Zorov, Dmitry B.
Abstract : The intercellular communications of mesenchymal multipotent stromal cells (MMSCs) and neuronal cells were studied in vitro. Cocultivation of MMSCs and rat cortical neurons proved the existence of intercellular contacts providing transfer of cellular contents from one cell to another. The exchange by cellular compartments between neural and stem cells improved MMSCs' protective abilities for better rehabilitation after stroke. Abstract: : The goal of the present study was to maximally alleviate the negative impact of stroke by increasing the therapeutic potency of injected mesenchymal multipotent stromal cells (MMSCs). To pursue this goal, the intercellular communications of MMSCs and neuronal cells were studied in vitro. As a result of cocultivation of MMSCs and rat cortical neurons, we proved the existence of intercellular contacts providing transfer of cellular contents from one cell to another. We present evidence of intercellular exchange with fluorescent probes specifically occupied by cytosol with preferential transfer from neurons toward MMSCs. In contrast, we observed a reversed transfer of mitochondria (from MMSCs to neural cells). Intravenous injection of MMSCs in a postischemic period alleviated the pathological indexes of a stroke, expressed as a lower infarct volume in the brain and partial restoration of neurological status. Also, MMSCs after cocultivation with neurons demonstrated more profound neuroprotective effects than did unprimed MMSCs. The production of the brain-derived neurotrophic factor was slightly increased in MMSCs, and the factor itself was redistributed in these cells after cocultivation. The level of Miro1 responsible for intercellular traffic of mitochondria was increased in MMSCs after cocultivation. We conclude that the exchange by cellular compartments between neural and stem cells improves MMSCs' protective abilities for better rehabilitation after stroke. This could be used as an approach to enhance the therapeutic benefits of stem cell therapy to the damaged brain. Significance: The idea of priming stem cells before practical use for clinical purposes was applied. Thus, cells were preconditioned by coculturing them with the targeted cells (i.e., neurons for the treatment of brain pathological features) before the transfusion of stem cells to the organism. Such priming improved the capacity of stem cells to treat stroke. Some additional minimal study will be required to develop a detailed protocol for coculturing followed by cell separation.